Treatment and Non-Treatment Professionals in Texas: Race, Sex, Age, and Level of Education Influencing Attitudes About Addiction - Richards, Shauna N. (Journal of drug issues, 2021)
Using a two-step process, attitudes about addiction among Texas professionals working primarily with youth were examined. In Step 1, researchers examined attitudes about addiction in Texas (n = 1,078), across professionals working with youth. In Step 2, researchers selected a subset of treatment and non-treatment professionals (n = 522) and tested two hypotheses related to differences in attitudes between the two professional groups. Two research questions were also explored. Step 1 analyses revealed stronger endorsement of attitudes related to the psychological and sociological models, and that demographic variables were modest but significant predictors of attitudes about addiction. Step 2 analyses revealed that professional status and demographic variables were significant predictors of attitudes about addiction. Findings have implications for treatment seeking, treatment and non-treatment professional behavior toward adolescents with substance use issues, and the need for continuing education to reduce stigma.